Peran Sistem Informasi Manajemen Pemasaran di PT Pos Indonesia - Agung Wijoyo; Delia Permata Sari; Annisa Aulia Rahmah; Brian Juanda Saragih; Yosia Zepanya Damanik (Institut Nalanda, 2023)
Management Information Systems are systems that help managers collect, manage and utilize information for effective decision making. Based on the definition obtained, the implementation of the management information system at PT Pos Indonesia consists of creating a database network system between departments in operational activities. In an effort to develop PT Pos Indonesia, it has implemented a business innovation, namely bill payment services, not only providing letter delivery services at the Post Office, it can now serve all forms of bill payments. PT Pos Indonesia has also created an application to support services and make it easier for customers to carry out their transaction needs, these applications are PosAja and PosPay. Then the obstacles faced during the implementation of the information management system at PT Pos Indonesia often occur overtime or delays in the data processing process due to frequent network disruptions and frequent system maintenance on applications, sudden changes in the system environment, and frequent policy changes in A management system that is less consistent makes it a bit difficult for employees.